1998
DOI: 10.1242/dev.125.9.1599
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of bHLH-PAS protein subcellular localization duringDrosophilaembryogenesis

Abstract: The Drosophila Single-minded and Tango basic-helix-loop-helix-PAS protein heterodimer controls transcription and embryonic development of the CNS midline cells, while the Trachealess and Tango heterodimer controls tracheal cell and salivary duct transcription and development. Expression of both single-minded and trachealess is highly restricted to their respective cell lineages, however tango is broadly expressed. The developmental control of subcellular localization of these proteins is investigated because o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The nuclear localization of Tgo coincides with the expression of Sim at stages 10B-12 and stage 14 (Fig 1B-E), which is consistent with our previous report (Knapp et al, 2020). Previous work showed that Tgo nuclear localization depends on Sim in CNS midline precursor cells (Ward et al, 1998). To test whether Sim is also required for Tgo nuclear localization in follicle cells, we examined the Tgo expression in sim -knockdown follicle cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The nuclear localization of Tgo coincides with the expression of Sim at stages 10B-12 and stage 14 (Fig 1B-E), which is consistent with our previous report (Knapp et al, 2020). Previous work showed that Tgo nuclear localization depends on Sim in CNS midline precursor cells (Ward et al, 1998). To test whether Sim is also required for Tgo nuclear localization in follicle cells, we examined the Tgo expression in sim -knockdown follicle cells.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work showed that Tgo nuclear localization depends on Sim in CNS midline precursor cells (Ward et al, 1998). To test whether Sim is also required for Tgo nuclear localization in follicle cells, we examined the Tgo expression in sim-knockdown follicle cells.…”
Section: Tgo Is Dynamically Co-expressed With Sim In Follicle Cells D...mentioning
confidence: 99%
See 1 more Smart Citation
“…Although jaywalker has been described earlier (Salzberg et al, 1994), we suggest renaming the jaywalker alleles as tango alleles due to the extensive literature on tango (Crews, 1998). Tango encodes a PAS‐bHLH protein and is known to act as an interaction partner of the several other PAS‐bHLH proteins: Single Minded, which controls CNS midline formation, Trachealess, which controls tracheal development, and Sima, which controls hypoxic responses (Lavista‐Llanos et al, 2002; Ohshiro and Saigo, 1997; Ward et al, 1998).…”
Section: Identification Of Tangomentioning
confidence: 99%
“…6). In most cells, it is expressed within the cytoplasm and in only a few tissues, such as the trachea and the CNS midline, Tango is localized within the nucleus (Ward et al, 1998). In addition, some peripheral glial cells express nuclear Tango protein (see Fig.…”
Section: Tango Acts In the Peripheral Glial Cellsmentioning
confidence: 99%